Fun Game Sebagai Peningkatan Kekompakan Dan Kerja Sama Pkk Kadus Iv Desa Sindon - Pramesti Regita Sari; Faqih Purnomosidi (Jurnal Nusantara Berbakti, 2024)
PKK is a sub-district community organization that is able to mobilize sub-district community participation in development, and also plays a role in sub-district growth activities. The PKK organization has been institutionalized at the central, provincial, district, sub-district and sub-district levels. The PKK organization in Sindon Village consists of several PKK groups which exist according to the division of cadres. In Sindon Village there are several hamlets, where ward IV itself includes 3 (three) hamlets, namely Sambiroto, Brajan and Manukan. In each hamlet there are several Neighborhood Units (RT), Sambiroto Hamlet has 3 RTs, Brajan Hamlet has 2 RTs and Manukan Hamlet has 2 RT. Where each RT in the hamlet has its own PKK group. This service activity is located in the MI 2 Sindon yard which is in Sambiroto Hamlet. This service activity was attended by 24 participants from three hamlets. The aim of this service is as a means of increasing the cohesiveness and cooperation of PKK Kadus IV Sindon Village